The Arabidopsis Embryo Mutant schlepperless Has a Defect in the Chaperonin-60α Gene - Apuya, Nestor R. (American Society of Plant Physiologists, 2001)
We identified a T-DNA-generated mutation in the chaperonin-60α gene of Arabidopsis that produces a defect in embryo development. The mutation, termed schlepperless (slp), causes retardation of embryo development before the heart stage, even though embryo morphology remains normal. Beyond the heart stage, the slp mutation results in defective embryos with highly reduced cotyledons. slp embryos exhibit a normal apical-basal pattern and radial tissue organization, but they are morphologically retarded. Even though slp embryos are competent to transcribe two late-maturation gene markers, this competence is acquired more slowly as compared with wild-type embryos. slp embryos also exhibit a defect in plastid development–they remain white during maturation in planta and in culture. Hence, the overall developmental phenotype of the slp mutant reflects a lesion in the chloroplast that affects embryo development. The slp phenotype highlights the importance of the chaperonin-60α protein for chloroplast development and subsequently for the proper development of the plant embryo and seedling.